Hypoglycemic Education Of Hypoglycemia Events - Santoso, Puguh; Setyowati, Novita (Universitas STRADA Indonesia, 2019)
To prevent the complications of hypoglycemia in people with diabetes, good and proper health education can increase the awareness of people with diabetes to want to change behavior in undergoing treatment programs so that sugar levels can be controlled and prevent various acute complications, especially complications of hypoglycemia. Increased knowledge is the basic principle of overcoming hypoglycemia in patients with diabetes mellitus independently and intensively. Education and behavior have shown a reduced risk of hypoglycemia for patients with diabetes mellitus. The purpose of this study was to determine the effect of hypoglycemic education on the incidence of hypoglycemia. This study used a Quasi Experiment design, the experimental design used was The Pretest-Posttest design without a control group. The technique used was total sampling. The sample used in this study was DM sufferers who came to Posyandu Lansia Desa Balowerti who had health problems with diabetes mellitus. Bivariate analysis was performed with a statistical test dependent sample t-test (paired t test.) The number of samples taken was Diabetes Mellitus patients who came to the posyandu of elderly balowerti, with a total of 20 respondents. The study was conducted in September 2019. The statistical test results obtained p value of 0.048, which means p value is less than alpha (P <0.05) which means Ho is rejected, so it can be concluded that there are differences in blood sugar levels of patients with diabetes mellitus before education and after diabetes exercise posyandu elderly balowerti village of Kediri .